A cross-sectional study design to determine the prevalence of knowledge, attitude, and the preventive practice of food poisoning and its factors among postgraduate students in a public university in Selangor, Malaysia - Mshelia, Arhyel Buba; Osman, Malina; Misni, Norashiqin (Public Library of Science, 2022)
Objectives: This study is designed to determine the knowledge, attitude, and practice of food poisoning and its factors among postgraduate students in Universiti Putra Malaysia. Methods: A cross-sectional study was conducted among 212 respondents who were selected through simple random sampling. Data was generated using a validated and reliable self-administered questionnaire. Results: The majority of the respondents are male, aged less than 35 years old, non-Malaysian, single, first-degree holders, not working, received a monthly income of less than 3264 Malaysian Ringgit, aware of food poisoning outbreak and the sources of their information of the food poisoning outbreak were television, the internet, newspaper, Online journals, friends, Facebook, community, nurse, drinking raw milk for the second time, information from their parents, relatives, restaurant, and radio. Majority had previous history of food poisoning illness but didn’t correctly confirm the causes of their food poisoning illness. Majority had poor knowledge, acceptable attitude, and good practice of food poisoning. A significant association was observed for citizen, marital status, awareness of food poisoning outbreak, and previous history of food poisoning illness with knowledge. Gender and awareness of food poisoning outbreak were significantly associated with attitude. Attitude and practice were significantly associated. Logistic regression revealed that being married, awareness of food poisoning outbreak, and previous history of food poisoning illness are predictors for good knowledge. Female respondents and awareness of food poisoning outbreak are predictors for acceptable attitude. Conclusion: Documentation of the identified poor knowledge and factors affecting knowledge, attitude, and practice provides essential information on the baseline indicators towards the risk of food poisoning among the respondents. A relevant interventional program is highly recommended to prevent the potential risks of food poisoning outbreak among them.